2019
DOI: 10.5535/arm.2019.43.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Combined Degeneration Caused by Nitrous Oxide Intoxication: A Report of Two Cases

Abstract: We report two cases of subacute combined degeneration (SCD) caused by nitrous oxide (N2O) gas intoxication, which is rarely reported in Korea. Two patients recreationally inhaled N2O gas daily for several months. They presented with paresthesia of limbs, voiding difficulty, and gait disturbance. The initial vitamin B12 levels were normal or decreased, but homocysteine levels of the two patients were increased. Magnetic resonance imaging of the cervical spine showed T2-weighted hyperintensity in the bilateral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…6 Multiple case studies have reported that the neurological and psychiatrical disorders, such as subacute combined degeneration, myelopathy, demyelinating polyneuropathy and emotional disorders, are related to N 2 O abuse. [7][8][9][10] There have even been deaths related to N 2 O inhalation. 11 Considering about the lack of awareness of N 2 O-abusing toxicity, we conducted a clinical study, which included a comprehensive and updated review of N 2 O abuse-induced neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…6 Multiple case studies have reported that the neurological and psychiatrical disorders, such as subacute combined degeneration, myelopathy, demyelinating polyneuropathy and emotional disorders, are related to N 2 O abuse. [7][8][9][10] There have even been deaths related to N 2 O inhalation. 11 Considering about the lack of awareness of N 2 O-abusing toxicity, we conducted a clinical study, which included a comprehensive and updated review of N 2 O abuse-induced neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biochemically, highly elevated tHcy is seen first in patients who abuse N 2 O, followed by a slow decrease in serum B 12 and holoTC, as well as slight elevations in MMA. Serum B 12 is often normal at presentation [218,219], which may lead to an incorrect differential diagnosis. It has been also suggested that inactive Me-Cbl is converted to Ado-Cbl [216].…”
Section: Protein Pump Inhibitors and H 2 -Receptor Antagonistsmentioning
confidence: 99%
“…Patients presenting with N 2 O‐induced SCD typically have a history of regular N 2 O abuse for several months. Neurological symptoms most commonly include paresthesia of the limbs, diminished proprioception and vibration sensation, ataxia, and later muscle weakness . Autonomic dysfunction and cognitive impairment may also be present .…”
Section: Introductionmentioning
confidence: 99%
“…Patients may have normal to low vitamin B12 levels, but methylmalonic acid and/or homocysteine levels are typically elevated and provide a more effective method to diagnose or screen for functional B12 deficiency . Inactivation of vitamin B12 ultimately leads to swelling of myelin sheaths and patchy myelopathic spongy vacuolation with demyelination, axonal swelling, and eventually axonal death …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation